1996
DOI: 10.1093/oxfordjournals.eurheartj.a014975
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of peripheral vasodilatory reserve capacity after cardioversion of atrial fibrillation

Abstract: In atrial fibrillation, exercise capacity is often reduced. This is usually ascribed to a decreased cardiac output as compared with sinus rhythm. Very few studies, however, have focused on changes in the peripheral blood flow during atrial fibrillation as a potential mechanism for exercise limitation. The aim of the present study was to determine the effect of conversion of atrial fibrillation to sinus rhythm on peripheral blood flow. Calf blood flow, using an electrocardiogram-triggered venous occlusion pleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Additionally, since peak VO 2 represents the product of cardiac output and arterial-venous oxygen content difference, a greater impairment of peripheral oxygen availability or utilization in AF may also be important. Endothelial dysfunction 40 and peripheral muscle blood flow abnormalities have been correlated with exercise performance in patients with chronic AF, although in the absence of structural heart disease 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since peak VO 2 represents the product of cardiac output and arterial-venous oxygen content difference, a greater impairment of peripheral oxygen availability or utilization in AF may also be important. Endothelial dysfunction 40 and peripheral muscle blood flow abnormalities have been correlated with exercise performance in patients with chronic AF, although in the absence of structural heart disease 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A contribution of peripheral changes resulting from this arrhythmia to the pathogenesis of exercise intolerance is undefined, although there are good reasons to believe that this is a possibility. In fact, the intermittent peripheral blood flow dynamics might affect the shear stress flow-mediated vascular control, impair the blood flow redestribution to exercising muscles (13,35), and sustain changes in muscle myofibrillar energetics (25). An irregular ventricular activity as induced by atrial fibrillation leads to a significant increase of the sympathetic outflow, which is responsible for an abnormal reflexogenic cardiovascular control and neural imbalance (37).…”
mentioning
confidence: 99%
“…In the performed analyses we demonstrated that the values of the plethysmographic indices during AFib in comparison to the values obtained after restoring sinus rhythm did not differ significantly. Amongst available literature, there is a limited number of studies discussing the plethysmographic assessment of peripheral flow in patients with AFib [5][6][7][8]. What is more, only small groups of patients were examined and the main aim of these investigations was the assessment of vasodilatation reserve and analysis of the function of endothelium in patients with arrhythmia and after restoring sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Gosselin and co-authors [5] analyzed blood flow through the calf during rest and after exercise in 28 patients with chronic AFib, with repeat measurements performed after restoring sinus rhythm. As their investigative method, they have used straingauge plethysmography, in which the inflation and deflation of the cuff that temporarily cut off the circulation were performed within 5 to 6 heartbeats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation